The Effect of Principal Supervision and Work Culture Through Achievement Motivation on the Performance of Javanese Language Subject Teachers in Temanggung Regency - baktiyono, budi wiyoto; Fakhrudin, Fakhrudin; Edy Mulyono, Sungkowo (Educational Management, 2024)
The aim of this study is to examine and evaluate the impact of principal supervision and work culture on performance, both directly and indirectly, with achievement motivation serving as a mediating factor. Several variables contribute to low teacher performance, such as inadequate principal oversight, unfavorable work culture, and insufficient teacher accomplishment incentive. This study employs a descriptive quantitative research approach, utilizing numerical data and statistical analysis through SPSS version 25. The focus of this study is on Javanese language instructors in both public and private junior high schools in Temanggung Regency, with a total of 104 individuals. The findings of this study suggest that principal supervision, work culture, and achievement motivation have a direct impact on teacher effectiveness. Indirectly, achievement motivation does not have the ability to mediate the influence of independent variables on the dependent variable. The findings indicate a clear and substantial correlation between principal supervision and work culture with teacher performance. However, it is important to note that the presence of an intervening variable, such as achievement motivation, does not mitigate the relationship between principal supervision and work culture on teacher performance.